Timeliness of Care Planning upon Initiation of Chronic Opioid Therapy for Chronic Pain - Von Korff, Michael (Pain Med, 2016)
Background. Chronic opioid therapy (COT) guidelines recommend developing a COT care plan at the initiation of COT. Objective. Assess the timeliness of care planning upon initiation of COT. Design. Observational cohort study in a setting incentivizing and tracking documentation of COT care plans in electronic health records (EHRs). Participants. Study participants (N = 896) were aged 45 years or older, had initiated an episode of opioid use within the prior 6 months, and reported regular use of prescription analgesics when screened for a baseline interview about 3 months after an index opioid prescription Measures. A timely care plan was defined by an EHR documented care plan prior to or within 4 months after the index opioid prescription. Results. Among COT initiators, 30% had a timely COT care plan documented in the EHR within 4 months following index prescription, while 51% had a documented COT care plan within 12 months following index prescription. Among those interviewed at 1 year follow-up (N = 735), 252 (34.2%) reported opioid use on 7 or more days in the prior 2 weeks. Less than half (45.6%) of the 252 individuals who sustained regular opioid use at 1 year had predicted at baseline that it was somewhat, very, or extremely likely they would be using opioids regularly in 1 year. Conclusions. Patients initiating COT were unlikely to have timely COT care plans. Many who sustained regular opioid use at 1 year had not anticipated using opioids long term.